2002
DOI: 10.1046/j.1471-6712.2002.00101.x
|View full text |Cite
|
Sign up to set email alerts
|

Do multidisciplinary integrated care pathways improve interprofessional collaboration?

Abstract: Do multidisciplinary integrated care pathways improve interprofessional collaboration?This paper reports on the evaluation stage of an action research project on interprofessional collaboration in discharge planning. Findings from interviews with health care professionals working in the acute sector had revealed concerns about discharge planning and multidisciplinary teamwork. In the United Kingdom the National Health Service (NHS) Plan has reinforced the need for an integrated approach to health care. Effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
168
1
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 188 publications
(180 citation statements)
references
References 17 publications
7
168
1
4
Order By: Relevance
“…The influence of personal factors/relational skills as critical antecedents to ICP is consistent with the literature (Atwal & Caldwell, 2002;CIHC, 2010;Gaboury et al, 2011;Havens et al, 2010;Safran et al, 2006;Temkin-Greener et al, 2004), andMcGrail et al (2009) indicated that without strong relational skills, ICP will not be as effective. Beliefs in interprofessional collaboration was not found to be a significant predictor of ICP, which was surprising in light of previous research.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…The influence of personal factors/relational skills as critical antecedents to ICP is consistent with the literature (Atwal & Caldwell, 2002;CIHC, 2010;Gaboury et al, 2011;Havens et al, 2010;Safran et al, 2006;Temkin-Greener et al, 2004), andMcGrail et al (2009) indicated that without strong relational skills, ICP will not be as effective. Beliefs in interprofessional collaboration was not found to be a significant predictor of ICP, which was surprising in light of previous research.…”
Section: Discussionsupporting
confidence: 84%
“…Relational skills are a precursor to ICP (McGrail et al, 2009), and interprofessional practitioners must have already developed strong cooperation (Gaboury, Lapierre, Boon, & Moher, 2011) and communication skills (Atwal & Caldwell, 2002;Havens, Vasey, Gittell, & Lin, 2010). Trust is critical, and according to D' Amour, Goulet, Labadie, San Martin-Rodriguez, and Pineault (2008), ICP is possible only when there is trust in each other's competencies.…”
Section: Antecedents Of Icpmentioning
confidence: 99%
See 3 more Smart Citations